International handbook of development economics - Dutt, Amitava Krishna; Ros, Jaime; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2008)
This two-volume original reference work provides a comprehensive overview of development economics and comprises contributions by some of the leading scholars working in the field. Authors are drawn from around the world and write on a wide range of topics.
pt. 1. Introduction -- pt. 2. Alternative approaches to development -- pt. 3. Macroeconomics of growth and development -- pt. 4. Factors in development -- pt. 5. Sectors in development -- pt. 6. International issues -- pt. 7. Distribution and poverty -- pt. 8. The state, institutions and development -- pt. 9. Economic development experience.
Includes bibliographical references and indexes.
Keywords: Development economics; Economic development; Electronic books